Peningkatkan Literasi Digital Melalui Pelatihan Desain Poster Menggunakan Canva Bagi PKBM Bina Insan Mandiri - Frisma Handayanna; Maryanah Safitri (AMMA : Jurnal Pengabdian Masyarakat, 2025)
In the learning process, sometimes learning activities are boring or students are less interested in the learning process. This situation is because teachers rarely or do not have enough initiative in using media for students to process the delivery of material. Digital literacy includes three abilities, namely the competence to utilize technology, interpret and understand digital content and assess its credibility, as well as how to create, research and communicate with the right tools. The Canva application offers various advantages, such as a variety of attractive designs that can be adapted to needs in the educational sector. Canva as a solution to improve digital literacy of students at PKBM Bina Insan Mandiri Depok, namely teachers and students of the Sekolah Master Indonesia. This training provides basic knowledge and practical skills in utilizing digital technology creatively, so that students are more active and effective in their learning process. One form of digital-based learning media is digital posters, which can be created with the help of applications such as Canva. Digital posters combine visual elements, text, and images to convey messages in a creative way.